Pulmonary function tests in β thalassemia major and its correlation with serum ferritin levels - Gadiparthi, Manaswita; Bhaskaranand, Nalini; Kini, Pushpa G.; Hebbar, Shrikiran; Mundkur, Suneel C. (International Journal of Contemporary Pediatrics, 2019)
Background: Extensive studies are conducted on heart, liver and endocrine abnormalities in thalassemia owing to their direct effect on survival, however, lung dysfunction has never been focused upon and is one of the least understood complications in β thalassemia. There’s a vacuum for data on pulmonary function tests in β thalassemia major in literature from India. Authors aimed to study pulmonary function and type of abnormality in cases with β thalassemia major above the age of 8yrs and to correlate the result with age and serum ferritin levels. Methods: Demographic data, hemoglobin value, serum ferritin levels, chelation details and transfusion requirement were analyzed. Spirometry was performed using COSMED pulmonary function test (PFT). Results: Among the 34 subjects studied, 21 were boys, and 13 were girls. Mean serum ferritin levels of the group was 3610.82±2679.51ng/mL and did not show a significant correlation with age, years of transfusion, and years of chelation. Forced vital capacity (FVC), forced expiratory volume in 1st second (FEV1) % values were lower in boys when compared to girls. PFT showed a restrictive pattern in the study group (FEV1/FVC=>0.7) with significant involvement in 73.5% of cases (FEV1<80%). A statistically significant negative correlation was observed between age and FEV1% (r=-0.577, p=<0.01) highlighting the importance of duration of iron overload. However, there was no significant linear correlation between restrictive lung disease and serum ferritin level (r=-0.06, p=0.75). Conclusions: Restrictive pattern was the most common abnormality, and it did not correlate with serum ferritin. Pulmonary function monitoring would help in identifying children with significant morbidity and help in initiating an early intervention to improve the quality of life.